A 26-year-old man with multiple organ failure caused by Aeromonas dhakensis infection: a case report and literature review - Luo, Dan; Dai, Liwan (Frontiers in Medicine, 2024)
Background:Human infections are mainly caused by Aeromonas hydrophila（A. hydrophila）, Aeromonas caviae(A. caviae), and Aeromonas veronii(A. veronii). In recent years, Aeromonas dhakensis(A. dhakensis)has been recognized as widely distributed in the environment, with strong virulence. However, this bacterial infection usually does not appear in patients with pneumonia as the first symptom. Case Report:We report a 26-year-old male was admitted to the hospital with community-acquired pneumonia as the first symptom and developed serious conditions such as hemolytic uremic syndrome, multiple organ dysfunction, and hemorrhagic shock within a short period.He died after 13h of admission, and the subsequent metagenomic next generation sequencing（m-NGS）test confirmed the finally identified the pathogen of infection as A. dhakensis infection. Conclusion:Aeromonas is a rare pathogen in the diagnosis of community-acquired pneumonia. Hence, doctors need to expand their experience in difference between infections caused by pathogenic microorganisms.Medical attention is essential during the occurrence of respiratory symptoms that could be controlled by empirical drugs, such as cephalosporins or quinolones. When patients with community-acquired pneumonia present hemoptysis and multiple organ dysfunction in clinical treatment, an unusual pathogen infection should be considered, and the underlying etiology should be clarified at the earliest for timely treatment.